2014
DOI: 10.1124/jpet.114.216705
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Administration as a Route for Drug Delivery to the Brain: Evidence for a Unique Pathway for Albumin

Abstract: A variety of compounds will distribute into the brain when placed at the cribriform plate by intranasal (i.n.) administration. In this study, we investigated the ability of albumin, a protein that can act as a drug carrier but is excluded from brain by the bloodbrain barrier, to distribute into the brain after i.n. administration. We labeled bovine serum albumin with [ 125

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 40 publications
1
43
0
1
Order By: Relevance
“…The pathway by which GUO applied to the nostril reaches the CNS seems to be reached as fast as only 5 min post-injection. This result is in accordance with other studies, which demonstrated that different drugs could reach maximal CNS concentrations immediately after administration [37,38]. No significant difference was observed in GUO endogenous levels in the brain structures following IN [ 3 H] GUO solution administration in any condition tested in this work.…”
Section: Discussionsupporting
confidence: 82%
“…The pathway by which GUO applied to the nostril reaches the CNS seems to be reached as fast as only 5 min post-injection. This result is in accordance with other studies, which demonstrated that different drugs could reach maximal CNS concentrations immediately after administration [37,38]. No significant difference was observed in GUO endogenous levels in the brain structures following IN [ 3 H] GUO solution administration in any condition tested in this work.…”
Section: Discussionsupporting
confidence: 82%
“…This observation is contradictory to what is observed in muscle where PKC activation leads to increased uptake. The effects observed here are unique to insulin since studies completed with these inhibitors and 125 I-albumin have shown a completely different proffile in regards to uptake into the brain post intranasal administration [37]. …”
Section: Discussionmentioning
confidence: 99%
“…Daily, intranasal leptin at concentrations of 0.1 or 0.2 mg/kg body weight has been shown to decrease weight and food intake over a 28-day period independent of changes in serum leptin levels (27). Radioactive tracer experiments reveal the hypothalamus and olfactory bulbs contain the greatest amounts of leptin 15-30 min after intranasal leptin administration (3,28). The hippocampus also had increased levels, but these were not different from the total brain average.…”
Section: Leptinmentioning
confidence: 96%
“…However, brain endothelial cells have relatively low expression, and the BBB prevents albumin from crossing in vitro and in vivo. In order to bypass the BBB, recent studies show evidence for the uptake of albumin across the nasal epithelium (3,17). Uptake occurred through a saturable transport system rapidly to all regions of the brain, with the highest levels detected in the striatum and the olfactory bulb.…”
Section: Proteins and Peptides Albuminmentioning
confidence: 99%
See 1 more Smart Citation